Technical efficiency and performance of the inland fisheries sector in Mannar District of Sri Lanka - Umashankar, K.; Luxon Reval, S. (National Aquatic Resources Research & Development Agency (NARA), 2015)
This research has taken effort to quantify the technical efficiency of the inland fisheries sector in the Mannar district and to identify important socio-economic factors which determines final harvest of the fishermen. A structured questionnaire was designed and then pretested with selected respondents and having seen it applicable was administered to the sample community. A total of 192 fishing households were randomly selected from a database managed by NAQDA. The data were analysed within the frame work of Stochastic Frontier Production Function using Frontier 4.1c. The results from the efficiency model revealed that the stocked fingerlings, land, family labor, and training were found to be significant. When 1% increase in these variables increased the catch by 0.214, 0.025, 0.014 and 0.040% respectively. Likewise age and education were found to be significant in the inefficiency model and for a 1% increase in these variables also increased the harvest by 0.003 and 0.043 % respectively. In order to serve the needful of the local community it is suggested that fingerlings are to be introduced in excess of the optimal quantity and hatcheries could be established locally. Periodic maintenance and management of reservoirs' bed is inevitable. Government policy should also focus on ensuring easy accessibility to bank loans especially to young participants to expand their activities. Formal lending scheme would help avoiding the interferences of the informal lenders. Work of advisory service and training provisions could be extended by recruiting more extension personnel. The mean technical efficiency of the sector was estimated as 64%. This manifested that the Mannar inland fisheries sector still have room for considerable improvements.
Keywords: Stochastic production functions; Technical efficiency; Inland fisheries sector